Industrialization Program To Overcome Economic Gaps In Society - Dhoya Safira Tresna Lestari; Muhammad Hamdan Ainulyaqin (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2022)
This research was motivated by the current growth of industrialization. Along with the increasing growth in the industrial sector, people have specialization and increase in income. This study discusses how the rapidly growing industrialization program had an impact on solving economic problems, in terms of overcoming economic inequality. Through a descriptive approach and a sharia approach, the authors collected data using a library research method. Industrialization in the Islamic perspective must be in accordance with the maqashid sharia, as shown in the Quran which is beneficial for all parties. The results of this study explain that the industrialization program has a substantial impact on the economic growth of a country. With the growth of a country's economy, the country leads to prosperity. Where welfare is often represented through equalization of rights among the community in getting equal opportunities in any case, so that there are no gaps/inequalities in society.